Dominant Tree of Lime Stone Karst in Habitat of Kha Nyou (Laonastes Aenigmamus) at Mouang-Doy Village, Thakhek District, Khammouane Province, Lao PDR - Khotpathoom, Thananh; Thammavong, Viengsamone; Vorasane, Houan; Souvansay, Duoangphachan; Chanthavong, Bakham (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Dominant tree of limestone karst was carried out to study in the habitat of Kha Nyou or Laotian rock rat (Laonastes aenigmamus) in Mouang-Doy Village, Thakhek District, Khammouane Province, central Lao PDR during April and June 2020 using stratified random sampling. Twenty 10x10m sampling plots were placed separately for each forest type (limestone deciduous forest and semi - evergreen forest) within the habitat of Kha Nyou was studied during 2008 and 2010. Tree dominance was considered based on Important Value Index (IVI). A total of 332 individual trees (1660 individual/ha) representing 30 families, 40 genera and 54 species were found. However, three of these species were only classified to a genus (appendix 01 and 02). The dominant trees of limestone karst in habitat of Kha Nyou can be separated based on forest types. In the semi - evergreen forest were Diospyros rubra H. Lec., Memecylon ovatum Sm. and Walsura trichostemon Miq. (mean IVI=51.70, 22.41, 18.65 and 14.55, respectively), while in the limestone deciduous forest were Sterculia pexa Pierre, Spondias pinnata (L.F) Kurz, Zanthoxylum cf. myriacanthum Wall. ex Hk. f. and Trichilia connaroides (Wight & Arnott) (mean IVI=81.65, 26.28, 22.97 and 17.23, respectively).